Future minds and a new challenge to anti-natalism - Gould, Deke Caiñas (Bioethics, 2021)
Some futurists and philosophers have urged that recent developments in biotechnology promise advancements that challenge standard accepted views of human nature, the self, and ethical obligation. Additionally, some have urged that developments in artificial intelligence similarly raise interesting new challenges to our conceptions of the mind, morality, and the future direction for conscious entities generally. Some have even gone so far as to argue in defense of “artificial replacement,” which is the view that humanity should be prepared to “hand over the keys,” so to speak, to a new sort of intelligent collection of entities and that we should go extinct gracefully. These views suggest a new challenge to the anti-natalist view that people should stop procreating: perhaps humanity is obligated to not allow itself to go extinct quite yet, at least until we have ensured that these next stages of intelligent entity have emerged. When we take into consideration some possibilities for entities with minds relevantly different from our own, we confront a challenge to the asymmetry argument that concerns human-like minds. Call this the “future minds challenge to anti-natalism.” I will examine some assumptions that underlie such a challenge, and I will argue that some famous articulations of the anti-natalist stance should be revised in light of such technological advancements.